Socioeconomic position interacts with the genetic effect of a CRP gene common variant to influence C-reactive protein values - Miriam Cheaib; Nicola Hornung; Nico Dragano; Mirjam Frank; Per Hoffmann; Markus M. Nöthen; Raimund Erbel; Andreas Stang; Börge Schmidt (Scientific Reports)
Abstract Objectives: C-Reactive Protein (CRP) values are partly determined by variation at the CRP gene locus, but also influenced by socioeconomic position (SEP) and related lifestyle factors. As gene-by-SEP interactions have been suggested for traits associated with CRP and SEP (e.g., BMI, coronary artery disease), the aim of this study was to investigate the strength of a possible interaction between a CRP gene common variant (rs4287174) and SEP in their joint influence on CRP levels in a population-based study sample. Methods: Single nucleotide polymorphism rs4287174 was genotyped in 4065 participants (aged 45–75 years) of the Heinz Nixdorf Recall study, a population-based prospective cohort. SEP indicators (education and income), risk factors (i.e., body mass index (BMI), total cholesterol, diabetes mellitus, coronary artery calcification, current smoking, hypertension, diet, no exercise) and blood serum CRP (mg/dl) were assessed at study baseline. Interaction analysis was based on linear regression and on stratified analyses (genetic effect stratified by SEP and vice versa) adjusted for age and sex using loge(CRP + 1) as dependent variable. Results: Low SEP and rs4287174 T allele were both associated with higher CRP values. The strongest genetic effect was observed in the lowest educational group (≤ 10 years of education) with an exp(β) indicating 1.058-fold (95%-CI: 1.018; 1.100) average CRP values per additional T allele, while in the highest educational group (≥ 18 years) the association was considerably less strong (exp(β): 1.005 (95%-CI: 0.975; 1.037)). After including rs4287174-by-education interaction terms in the regression analysis, interaction was indicated suggesting stronger genetic effects on CRP in low SEP groups (exp(βinteraction): 1.056 (95%-CI: 1.005; 1.108); p = 0.029). The observed interaction did not seem to be substantially mediated by the risk factors included in the analysis. No indication for rs4287174-by-income interaction was observed. Conclusion: Results imply that genetic effects of the CRP locus are modified by education as an indicator of life course SEP.